Անիի քաղաքացիները. (քաղաքային տոհմեր) - Մաթևոսյան, Կարեն (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
История и культурное наследие Ани — столицы средневековой Армении, достаточно изучены в отличие от истории самих анийцев. В городе жила элита армянского общества от королей и членов их семей до аристократических домов, высокопоставленных священнослужителей — католикосов, епископов. Но более крупный городской слой состоял в основном из ремесленников и купцов, а также других небольших групп. Сведения о простых гражданах Ани сохранились в литографических надписях и памятных записях рукописей. Известны большие семьи или роды жителей Ани, в упоминании которых используются родовые имена. В статье представлена информация о таких семьях, как Бехенц, Оненц (они же Тигрананц), Чечканц, Огеворянц, Oромянц, Хотенц, Шехенц, Циленц, Торосонц. Также представлена семья врачей. Названия ряда родов сохранились в названиях принадлежащих им церквей, домов, магазинов и садов. The history and cultural heritage of Ani, the capital of medieval Armenia, has been sufficiently studied, whereas the same cannot be said about the history of the inhabitants of Ani. Although the city housed the elite of the Armenian society, i.e., kings, royal family members, aristocratic houses and high-ranking clergymen — Catholicos, bishops and archimandrites (vardapet), the larger strata of urban society consisted mainly of craftsmen and merchants, as well as other small groups. Information about ordinary citizens of Ani has been preserved in lithographic inscriptions and colophons of manuscripts. Notable families from Ani are known, who are mentioned by their family names. The article provides information about such families as the Bekhents, Honents (Tigranats), Chechkants, Hogevoryants, Horomyants, Khotents, Shekhents, Tsilents, Torosonts. The article also mentions a family of physicians. The names of a number of families have survived in the names of churches, houses, shops and gardens belonging to them.
Keywords: Christianity; History